Preferences of Istrian sheep udder shape type on farms that apply machine milking - Šalamon, Dragica; Džidić, Alen (Acta Agraria Kaposváriensis, 2014)
Istrian sheep is an indigenous endangered breed reared at extensive or semi-extensive farms in Croatia. The number of farms applying machine milking is increasing due to high quality dairy products. The objective of this work was to evaluate morphometry of the udder and milk flow kinetics in the Istrian sheep in Croatia, and to explore possible preferences of udder shape type on farms that apply machine milking. Using LactocorderÂ© (WMB; Switzerland) we measured milk flow kinetics in five commercial herds. Using digital photographs of the posterior view of the udder and Image Tool software we measured udder height, width, cisternal part below the teat orifice and the angle that teat closes with the vertical axis of the udder in eleven herds. Breeding values were estimated using univariate animal models and REML (Restricted Maximum Likelihood). Istrian sheep breed in Croatia has excellent udder shape for machine milking: desirable angle that teat closes with the vertical axis of the udder, and cisternal height below the teat orifice is small. Ewes that are machine milked have higher udder, lower cisternal part below the teat orifice, and teats are more vertically implanted, which is the udder conformation beneficial for more efficient machine milking. BLUP value differences indicated that machine milked herds tend to have ewes with smaller cisternal part below the teat orifice that are of less udder height in the beginning of lactation and wider at the end of lactation, although there is no official selection of udder shape.
Keywords: udder morphometry; milkability; BLUP; dairy ewe